Discursive work within weak field mandate events: The case of a conference on assistive technologies for persons with disabilities. Issue 4 (December 2018) - Kulkarni, Mukta
Abstract: The present study outlines discursive work in a weak field mandate event. The case is a conference focussed on assistive technologies that may help persons with disabilities gain better access to educational and employment spaces in India. Findings highlight three mechanisms which underpinned event-specific discursive work – discursive clarity, alignment, and coordination. In outlining such discursive work, the present study indicates how actors, who congregate as a group without high symbolic or resource support from powerful institutional elites, attempt to influence broader processes of institutionalisation.